Effective Management in the Implementation of Link and Match Curriculum for Quality Graduates - Andriyani, Fita; Leksono, Aris Adi (Journal of Education and Learning Innovation, 2024)
Nowadays, the development of the era demands a change in the education curriculum that emphasizes the need to build national character. This is based on facts and the views of the community regarding the decline in the moral quality and attitudes of the younger generation in keeping up with the times. Currently what is needed is an educational curriculum that is characterized in the sense that the curriculum itself has character and is at the same time oriented towards the formation of the character of educators. Curriculum development is an integral part of the curriculum itself (inherent), and an applicable curriculum must be continuously improved. by adopting the needs that develop in society. The implementation of education in Vocational High Schools is a process of learning and guidance in schools. The learning process in schools primarily aims to equip students to develop personality, academic potential, and a strong and correct foundation of expertise through learning.